An essay on financial innovation: The case of instalment receipts - Charupat, Narat; Prisman, Eliezer Z. (Journal of Banking & Finance, 2004)
We investigate the relative pricing of an innovated security called “instalment receipts” (IRs). IRs are securities that evidence the purchase of some underlying securities on an instalment basis. Theoretically, we show that investors with borrowing restrictions will be willing to pay for the leverage benefit embedded in IRs. We then provide an empirical support for our argument. The observed premium in IR price over the underlying price implies that by using IRs, the issuers benefit from both an increase in demand and a reduction in the price concessions that they have to make to ensure the success of their offerings.